2002
DOI: 10.1194/jlr.m20008-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trans-10,cis-12 conjugated linoleic acid induces hyperinsulinemia and fatty liver in the mouse

Abstract: Conjugated linoleic acids (CLA) are a class of positional, geometric, conjugated dienoic isomers of linoleic acid (LA). Dietary CLA supplementation results in a dramatic decrease in body fat mass in mice, but also causes considerable liver steatosis. However, little is known of the molecular mechanisms leading to hepatomegaly. Although c9,t11 -and t10,c12 -CLA isomers are found in similar proportions in commercial preparations, the respective roles of these two molecules in liver enlargement has not been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
310
6
19

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(380 citation statements)
references
References 43 publications
(48 reference statements)
45
310
6
19
Order By: Relevance
“…15 Similar results have been obtained in other studies in mice. 98,99 The tissue examination did not show any severe pathological changes but increased lipid droplets in the liver and spleen. 15,20 The biochemical, cellular and molecular mechanisms involved in the development of fatty liver and spleen are not well established.…”
Section: Cla Induces Insulin Resistancementioning
confidence: 99%
“…15 Similar results have been obtained in other studies in mice. 98,99 The tissue examination did not show any severe pathological changes but increased lipid droplets in the liver and spleen. 15,20 The biochemical, cellular and molecular mechanisms involved in the development of fatty liver and spleen are not well established.…”
Section: Cla Induces Insulin Resistancementioning
confidence: 99%
“…In contrast, Azain et al [4] did not find changes in FAS activity induced by CLA feeding in rats. Other authors found reduced expression of FAS and ACC in mice [5,6] . In the present work, trans-10,cis-12 CLA feeding significantly reduced the mRNA expression of the two specific lipogenic enzymes measured (ACC, FAS).…”
Section: Discussionmentioning
confidence: 86%
“…One of the mechanisms behind an increase in liver lipids may involve the reduction of leptin and adiponectin mRNA by t10, c12-CLA (Warren et al 2003). Also, the accumulation of fat in liver may be due to the hyperinsulinemia caused by CLA (Clément et al 2002) which SMP could not prevent as milk proteins are also insulinotropic (Nilsson et al 2004). Insulin activates fatty acid uptake in the liver possibly causing high fat deposition in liver of CLA and CLA + SMP groups.…”
Section: Resultsmentioning
confidence: 99%